Política Nacional de Educação Permanente e a educação permanente em saúde no Paraná - Moraes, Ana Cristina de (2022)
After the creation of the Unified Health System (SUS) it was required that professional training processes be implemented to qualify the workers already involved, as well as those who joined the system. Training based on the work environment, through a process of significant learning is called Permanent Education in Health, a process in which the reality and the challenges experienced are valued for professional development, aiming at improving the quality of health care. In the state of Paraná, Permanent Education in Health, its strategies and proposals are discussed and agreed based on the State Plan for Permanent Education, which deals with the regional needs of professional training. This study aims to understand how the actions to train workers for the SUS were introduced and implemented after the National Policy on Permanent Education in Health in the Health Regions in the State of Paraná. Exploratory and qualitative research, with intentional or purposeful non-probability sampling. Data were collected through interviews, through online platforms, with professionals who work or have worked with continuing education in health in regional health in the state of Paraná. was carried out through thematic content analysis. The results, presented in three articles. Article one called: Unified Health System and Permanent Health Education in Paraná: historical trajectory, permanent health education in the state gained visibility in regional centers and intensified after the meeting of projects in the Teaching Service Integration Commissions (CIES), little active, concluding that there is still a need for investments and appreciation of the shares. Article two entitled: Understandings, pedagogical assumptions and experiences of EPS in Paraná, it was problematized that EPS takes place on two fronts, one being a distance education experience, and the other that focuses on ESPP actions together with regional ones. of health and municipalities. Article three, called: Multiprofessional Residencies in Family Health: a strategy for the implementation of Permanent Health Education in Primary Care, in which it was concluded that the RMSF are concentrated in the territories assisted by higher education institutions or public health schools, requiring these spaces should be expanded; are important training environments to strengthen primary health care and the SUS. Permanent education is present in state actions prior to the creation of the policy; among the actions, distance education stands out, the role of the Escola de Saúde Pública do Paraná as a catalyst for actions and the Multiprofessional Residencies in Family Health as a possibility of expanding qualified training for Primary Health Care, and also the need for greater investments and discussions to revive permanent education in the state.